Gruenhage spaces and their influence on Banach space renorming theory - Smith, Richard (Topology Proceedings, 2025)
In a paper from 1987, Gruenhage defined a class of topological spaces that now bear his name, and used it to solve a problem of Talagrand on the existence of dense G_δ metrizable subsets of Gul’ko compact spaces. Gruenhage’s paper became highly influential among researchers in renorming theory, a branch of Banach space theory. In this paper we survey Gruenhage and related spaces, and their interactions with renorming theory.